Given:
The functions given are,
![\begin{gathered} f(x)=x-3 \\ g(x)=x+1 \end{gathered}](https://img.qammunity.org/2023/formulas/mathematics/college/kpvyci8xhj27f235cl50ifrwpqoqzf7x6v.png)
Required:
To find the value of
![(fg)(0)](https://img.qammunity.org/2023/formulas/mathematics/college/ij131l51yrnw4nq6sg5sgt6oxpibbi388i.png)
Step-by-step explanation:
We have two given functions as:
![\begin{gathered} f(x)=x-3 \\ g(x)=x+1 \end{gathered}](https://img.qammunity.org/2023/formulas/mathematics/college/kpvyci8xhj27f235cl50ifrwpqoqzf7x6v.png)
Therefore, the product of two functions is given by,
![\begin{gathered} (fg)(x)=f(x)\cdot g(x) \\ \Rightarrow(fg)(x)=(x-3)\cdot(x+1) \\ \Rightarrow(fg)(x)=x^2+x-3x-3 \\ \Rightarrow(fg)(x)=x^2-2x-3 \end{gathered}](https://img.qammunity.org/2023/formulas/mathematics/college/xodae4q253y7b6gv83crat7db2gat01ysc.png)
Thus, the value of the product of the functions at x = 0 is,
![\begin{gathered} (fg)(0)=(0)^2-2\cdot(0)-3 \\ \Rightarrow(fg)(0)=0-0-3 \\ \Rightarrow(fg)(0)=-3 \end{gathered}](https://img.qammunity.org/2023/formulas/mathematics/college/5u0dwlbmwwffrbn8uh8rxhjp3pwlte2ca5.png)
Final Answer:
The value of the product of the functions at x = 0 is,
![(fg)(0)=-3](https://img.qammunity.org/2023/formulas/mathematics/college/cn2kxoqhy0rls0l3e4fi20fodclpjc3zrn.png)